"Coffee Ring Effect" in Ophthalmology: "Anionic Dye Deposition" Hypothesis Explaining Normal Lid Margin Staining. Issue 14 (April 2016) - Rajabi, Mohammad Taher; Sharifzadeh, Morteza
Abstract : Abstract: The process of formation of Marx line is studied in this article. Various theories have been proposed previously, in order to explain the mechanisms which lead to the development of Marx line. These theories are based on the characteristics of stained area and do not pay attention to the behavior of dye solution itself on the surface. The aim of this study is to investigate the latter behavior and introduce a new theory based on it, in order to explain the process of the Marx line formation. This study also introduces "Coffee Ring Effect" and its possible applications in explaining some ophthalmological phenomena. The effect of dye solution's behavior on the beneath surface is adopted in order to propose a novel theory. This new hypothesis is called "Anionic Dye Deposition" which was based on "Coffee Ring Effect" phenomenon. For evaluation of this theory, Evaporation pattern of Rose Bengal and fluorescein were analyzed on different surfaces. Furthermore, the effect of tear meniscus alteration on lid margin staining is studied. During the evaporation process of dye solutions, it was observed that almost all of the solute was deposited at the edge of the drop on hydrophilic surfaces. Furthermore, in the study of lid margin staining, it is observed that tear meniscus alteration during gaze affects staining pattern. This observation invalidates former hypotheses which only focus on stained surface characteristics. According to the observations in this study, it is proposed that Marx line staining occurs as a result of "anionic dye deposition" due to evaporation.